2020
DOI: 10.7717/peerj.8756
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between healthcare seeking and pain expansion in patients with nonspecific chronic low back pain

Abstract: Objectives Low back pain (LBP) is the most prevalent musculoskeletal problem, which implies a high rate of chronicity. The chronicity of symptoms can lead to pain expansion. The main objective of this study was to assess whether there were differences between patients with nonspecific chronic LBP (CLBP) who sought healthcare compared to those who did not in terms of pain expansion. Methods Ninety individuals participated in the study and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 79 publications
1
4
0
1
Order By: Relevance
“…In addition, a new finding from this study indicates that trunk flexor endurance levels are connected with the frequency of SP. Other studies have also reported on the relevance of frequency and level of pain to other variables [28]. This supports the importance of the trunk flexor endurance on SP.…”
Section: Discussionsupporting
confidence: 75%
“…In addition, a new finding from this study indicates that trunk flexor endurance levels are connected with the frequency of SP. Other studies have also reported on the relevance of frequency and level of pain to other variables [28]. This supports the importance of the trunk flexor endurance on SP.…”
Section: Discussionsupporting
confidence: 75%
“…The inclusion criteria were: 1) to have had LBP for at least the prior six months (28); 2) LBP of a nonspecific nature (28); 3) to be aged 18–65 years (29); 4) to suffer pain intensity of between 3 and 10 on the visual analogue scale (30); and 5) to have one hip with limited active internal rotation, measured by goniometer (31). The exclusion criteria were: 1) to have peripheral pain (like a sciatic pain); 2) the presence of neurological signs or muscular dystrophy, systemic rheumatic disease or central nervous system disease (32); 3) electrophysiological findings referable to another peripheral nerve; 4) any previous surgery or acute trauma in the trunk or lower extremity; 5) commonly accepted contraindications to invasive physical therapy techniques (21); 6) any contraindications to needling per se (21); and 7) epilepsy.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the evidence and our results, we suggest that selfefficacy is a determinant in terms of the disability perceived by these patients (Woby et al, 2007;de Moraes Vieira et al, 2014). In terms of kinesiophobia, studies have shown that fear of movement is one of the most influential psychological factors in terms of disability in patients with chronic pain (Sullivan et al, 2009;Grande-Alonso et al, 2020;Nieto-García et al, 2019). In support of our results, Sullivan et al reported that patients with CLBP who have greater kinesiophobia have a greater perception of pain than patients with CLBP who do not have kinesiophobia (Sullivan et al, 2009).…”
Section: Discussionmentioning
confidence: 55%